พัฒนาการโครงการกายภาพเชิงสร้างสรรค์ฟื้นฟู ย่านชุมชนเมือง กรุงเทพมหานคร - คมเดช ด่านศักดิ์ชัย (คณะสถาปัตยกรรมศาสตร์ จุฬาลงกรณ์มหาวิทยาลัย, 2022)
This article examines roles and responsibilities of the BMA in allocating an annual budget towards creative tangible projects in the city. Creative tangible projects in urban communities developed during year 2017-2020 were selected to analyze the alteration of budget management. Surveying, data collecting, and reviewing literature consisting of power decentralization specified in Thailand constitution year 20 Bangkok action plan, procurement budget regulation during 2017-2020, and an annual budget allocation were carried out. This is to get an insight into the roles of the BMA, as well as, other related public and private agencies getting involved in the process of budget allocation. The results showed that the BMA could appropriately set a local budget to complete revitalized projects in the city. The BMA has also tried to balance the budget allocated to those creative tangible projects by reducing the amount and financial flows spending for regular urban revitalized works. This considerably makes budget allocation more efficient and beneficial for all residents living in the area of Bangkok. The BMA has an important role in encouraging public and private participation, particularly allowing those two parties join the process of project planning, design, and construction. Moreover, the integration of participation through the 20-year national strategic plan brings variety and creativity to city development. This paper recommends the BMA to improve quality of urban communities, and promote public participation between public and private sectors, as well as local people. Moreover, revitalized projects should be conducted in creative and sustainable way to support the future urban growth.